2017
DOI: 10.1016/j.bbapap.2017.02.007
|View full text |Cite
|
Sign up to set email alerts
|

The papain-like cysteine proteinases NbCysP6 and NbCysP7 are highly processive enzymes with substrate specificities complementary to Nicotiana benthamiana cathepsin B

Abstract: The tobacco-related plant Nicotiana benthamiana is gaining interest as a versatile host for the production of monoclonal antibodies and other protein therapeutics. However, the susceptibility of plant-derived recombinant proteins to endogenous proteolytic enzymes limits their use as biopharmaceuticals. We have now identified two previously uncharacterized N. benthamiana proteases with high antibody-degrading activity, the papain-like cysteine proteinases NbCysP6 and NbCysP7. Both enzymes are capable of hydroly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 52 publications
1
26
0
Order By: Relevance
“…Recombinant NbCysP6 Generates Acyclic kB1 from Synthetic LQLK-kB1. NbCysP6 is a cathepsin L-like papain-like cysteine protease (PLCP) from the RD21 subclass (25,26). Like most members of this subclass (25), the domain architecture of NbCysP6 consists of an Nterminal signal peptide, an autoinhibitory I29 domain, a C1 protease domain, a proline-rich segment, and a cysteine-rich C-terminal granulin domain.…”
Section: Resultsmentioning
confidence: 99%
“…Recombinant NbCysP6 Generates Acyclic kB1 from Synthetic LQLK-kB1. NbCysP6 is a cathepsin L-like papain-like cysteine protease (PLCP) from the RD21 subclass (25,26). Like most members of this subclass (25), the domain architecture of NbCysP6 consists of an Nterminal signal peptide, an autoinhibitory I29 domain, a C1 protease domain, a proline-rich segment, and a cysteine-rich C-terminal granulin domain.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it is noteworthy that the papain with the code Medtr1g018840.2 appears both in cell extract and culture medium, which might indicate that this specific protease is in transit within the cell. Furthermore, it has already been established that PLCPs are able to degrade antibody molecules …”
Section: Resultsmentioning
confidence: 99%
“…Using activity‐based probes, enzymatically active forms of the two PLCPs NbALP and NbCysP6 have been detected in the apoplast of N. benthamiana leaves . We have previously shown that recombinant NbALP and NbCysP6 are capable of cleaving the bNAb 2F5 in its CDR H3 loop . However, the insensitivity of 2F5 processing to the general PLCP inhibitor E‐64 contradicts a major contribution of NbALP and NbCysP6 to CDR H3 cleavage in planta.…”
Section: Discussionmentioning
confidence: 99%
“…[41] We have previously shown that recombinant NbALP and NbCysP6 are capable of cleaving the bNAb 2F5 in its CDR H3 loop. [44,45] However, the insensitivity of 2F5 processing to the general PLCP inhibitor E-64 [20] contradicts a major contribution of NbALP and NbCysP6 to CDR H3 cleavage in planta.…”
Section: Discussionmentioning
confidence: 99%